Effects of Tissue Flossing on the Healthy and Impaired Musculoskeletal System: A Scoping Review - Konrad, Andreas; Močnik, Richard; Nakamura, Masatoshi (Frontiers in Physiology, 2021)
There is a belief that tissue flossing can improve range of motion or performance, speed up recovery, and decrease pain caused by various diseases or injuries. As a result, many therapists, patients, and athletes are now using this technique. Consequently, in the last five years, a number of studies have addressed these assumptions. The purpose of this scoping review is to introduce the application of a floss band and to summarize the existing evidence for the effect of floss band treatment on range of motion, performance, recovery, and pain (due to disease or injuries). A further goal is to suggest what needs to be addressed in future studies. The online search was performed in the PubMed, Scopus, and Web of Science databases. Any studies dealing with the effects of a floss band treatment on range of motion, performance, recovery, or pain parameters in any population (e.g. patients, athletes) were included in this review. Twenty-four studies met the inclusion criteria, with a total of 513 participants. The included studies revealed that there is evidence that a single floss band treatment is able to increase the range of motion of the related joint and can positively affect jumping and strength performance. However, these findings show only small to moderate effect sizes. Although not yet clearly understood, a possible mechanism for such changes in range of motion or performance is likely due to changed neuromuscular function, rather than changed mechanical properties of the muscle (e.g. stiffness). All in all, there is a need to conduct long-term studies about the effects of flossing treatment on range of motion and performance (e.g. strength or jumping parameters) and its related mechanism (e.g. pain tolerance). There is weak evidence that flossing can be of value for pain relief in the treatment of certain diseases, and for speeding up recovery after exercise. Moreover, there is weak evidence that flossing might have a superior conditioning (warm-up) effect compared to stretching when the goal is to improve range of motion or certain aspects of muscle strength, while no such superior effect has been reported when compared to foam rolling.